Automatic main failure (AMF) system - Saiful Anuar, Alwi (2008)
Recently, solar energy has become one of the important alternative power supply for many devices due to the rises of fuel price. The limitedness of this kind of energy is its depend on the existence or the brightness of sunlight. This thesis presents a way to keep any 12V devices powered by solar power get the continuous power. The purposes of this project are to design and build a system that called Automatic Main Failure (AMF) System which can automatically allow switching from solar cell power supply to a battery as backup power supply. To execute this system, there are three main elements is used which are voltage sensor, micro controller and relay switch. The system is continually monitoring the voltage level from solar cell. If the voltage is dropped below the allowed level, this system will switch the device to battery and switch back to solar cell when the level voltage is back to normal. If the voltage from solar cell is higher than allowed level, the voltage will be regulated to normal level through a voltage regulator. Thus the device will get a continuous power and protected from the effects of under-voltage and over-voltage.